Production of edible fungal (Rhizopus delemar CBS 145940) biomass from organosolv-pretreated oil palm empty fruit bunch (OPEFB) in submerged fermentation. Issue 1 (December 2020) - Marhendraswari, MB D; Mondylaksita, K; Millati, R; Budhijanto, W; Ferreira, J A; Niklasson, C; Taherzadeh, M J
Abstract: Accumulation of oil palm empty fruit bunches (OPEFB) from palm oil industry poses challenges for the disposal process, which leads to environmental damage. For this reason, valorization of OPEFB fractions to produce edible fungal biomass was carried out in this research. The fungus was Rhizopus delemar CBS 145940, which is an edible fungus, Indonesian indigenous, and is favorable for the production of several end products. Organosolv pretreatment was first conducted on OPEFB using ethanol (50%) as the solvent. Enzymatic hydrolysis was then performed using Cellic® Ctec3 on the pretreated-OPEFB fractions. Hydrolyzates from cellulose-rich fraction, slurry (a mixture of cellulose-rich fraction and hemicellulose-rich fraction), and hemicellulose-rich fraction were used as the cultivation media for fungal growth. The corresponding yield of fungal biomass from each medium was 0.62 ± 0.07 g/g glucose; 0.41 ± 0.02; and 0.61 ± 0.13 g/g fermentable sugars, respectively. These results showed that Rhizopus delemar CBS 145940 could be grown in all the hydrolyzates from the OPEFB fractions. Nevertheless, in order to obtain higher fungal biomass, supplementation of nutrition was needed.